The library of unruly treasures - Birdsall, Jeanne (Alfred A. Knopf, 2025)
"Gwen MacKinnon's parents are dreadful. Truly, deeply, almost impressively dreadful. So Gwen's not upset at all when she's foisted onto her never-before-seen Uncle Matthew for two weeks. Especially when it turns out he has a very opinionated dog named Pumpkin. Things take a turn for the weird when Gwen makes a discovery in the local library. A discovery that involves tiny creatures with wings. And no, they're not birds. They're called Lahdukan. But why can only Gwen and the youngest children, gathered for storytime, see them? The Lahdukan insist that Gwen is destined to help them find a new home. But how can a girl as unwanted, uncourageous, and generally unheroic as Gwen possibly come to the rescue? Pumpkin has a few ideas..."--